2022
DOI: 10.1155/2022/7495418
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Comprehensive Care Based on Appropriate Chinese Medicine Techniques on Urinary Retention and Bladder Function Recovery after Total Hysterectomy in Patients with Cervical Cancer

Abstract: Objective. To investigate the effect of comprehensive care based on appropriate Chinese medicine techniques on urinary retention and bladder function recovery after total hysterectomy in patients with cervical cancer. Methods. A total of 148 cases admitted after radical hysterectomy for cervical cancer from January 2019 to early September 2019 were used as the observation sample and were divided into control and experimental groups based on a randomized double-blind method. There were 74 cases each. The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%